Pengaruh Leverage Dan Sales Growth Terhadap Tax Avoidance Pada Perusahaan Farmasi Yang Terdaftar Di Bursa Efek Indonesia Periode Tahun 2016-2020 - Fenty Jayani; Daryanto Hesti Wibowo (Jurnal Ilmu Administrasi Publik, 2021)
This study aims to determine the effect of leverage and sales growth both partially and simultaneously on tax avoidance among pharmaceutical companies listed on the Indonesia Stock Exchange for the period 2016-2020. This study used quantitative methods with secondary data from 6 samples of pharmaceutical company financial statements. Sampling was done using purposive sampling technique. The data analysis technique used included panel data regression analysis and classical assumption tests with the help of the EViews 9 program. The results show that partially the Leverage variable has a negative and significant effect on Tax Avoidance, while the Sales Growth variable has a positive and significant effect on Tax Avoidance. Simultaneously, Leverage and Sales Growth variables have a significant effect on Tax Avoidance. This can be seen from the t-test on Leverage (X1) and Tax Avoidance (Y) variables, which produced a tcount value of -2.44 (greater than ttable 2.05) and a significance value of 0.02 (less than 0.05). Meanwhile, the t-test on Sales Growth (X2) and the Tax Avoidance (Y) variables resulted in a tcount value of 3.38 (greater than ttable 2.05) and a significant value of 0.00 (less than 0.05). In the F test, the Fcount value is 5.96 (greater than Ftable 4.20) and the significance value is 0.02 (less than 0.05).